Odpowiedź:
a1 = (√2)•1²+1 = √2 + 1
a2 = (√2)•2²+1 = 2²√2 + 1 = 4√2 + 1
a3 = (√2)•3²+1 = 3²√2 + 1 = 9√2 + 1
a4 = (√2)•4²+1 = 4²√2 + 1 = 16√2 + 1 to trzynasty wyraz cigu:
....................................................................
a13 = (√2)•13²+1 = 13²√2)+1 = 169√2 + 1
Szczegółowe wyjaśnienie:
an = (√2)n²+1 to podstawiając kolejne cztery liczby naturalne za
n = 1, 2, 3, 4 otrzymamy:
a1 = (√2)•1²+1 = √2 + 1
a2 = (√2)•2²+1 = 2²√2 + 1 = 4√2 + 1
a3 = (√2)•3²+1 = 3²√2 + 1 = 9√2 + 1
a4 = (√2)•4²+1 = 4²√2 + 1 = 16√2 + 1 to trzynasty wyraz cigu:
....................................................................
a13 = (√2)•13²+1 = 13²√2)+1 = 169√2 + 1